Revealing correlation effect of Co 3d electrons in La3Co4Sn13 and Ce3Co4Sn13 by infrared spectroscopy study. (1st September 2017) - Ban, W J; Luo, J L; Wang, N L
Abstract: We report resistivity, specific heat and optical spectroscopy measurements on single crystal samples of L a 3 C o 4 S n 13 and C e 3 C o 4 S n 13 . We observed clear temperature-induced spectral weight suppression below 4000 c m − 1 for both compounds in the conductivity spectra σ 1 ( ω ), indicating the progressive formation of gap-like features with decreasing temperature. The suppressed spectral weight transfers mostly to the higher energy region. This observation reflects the presence of the correlation effect in the compounds. We attribute the correlation effect to the Co 3d electrons.